2010
DOI: 10.4103/0255-0857.58729
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility testing of rapidly growing mycobacteria by microdilution -$$$ Experience of a tertiary care centre

Abstract: We wish to emphasize that reporting of rapidly growing mycobacteria from clinical settings, along with their sensitivity patterns, is an absolute need of the hour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 6 publications
1
6
0
1
Order By: Relevance
“…With regard to tetracycline, the present study showed tigecycline antimicrobial activity, while minocycline and doxycycline did not, as previously reported by Wallace et al (2002). The isolate was resistant to imipenem which is in accordance with a previous study (Set et al 2010). Among aminoglycosides, amikacin was active, whereas tobramycin showed intermediate activity.…”
Section: Discussionsupporting
confidence: 92%
“…With regard to tetracycline, the present study showed tigecycline antimicrobial activity, while minocycline and doxycycline did not, as previously reported by Wallace et al (2002). The isolate was resistant to imipenem which is in accordance with a previous study (Set et al 2010). Among aminoglycosides, amikacin was active, whereas tobramycin showed intermediate activity.…”
Section: Discussionsupporting
confidence: 92%
“…We have also found M. fortuitum resistant to clarithromycin. [63] Many studies have shown that M. fortuitum contains an inducible erythromycin methylase gene erm which may confer macrolide resistance. Some investigators believe that differences in antibiotic resistance rates in RGM maybe the result of population or geographical differences or may be due to the method of susceptibility testing.…”
Section: Resultsmentioning
confidence: 99%
“…En este estudio, 8 de las 14 cepas (57%) de M. abscessus fueron inhibidas por IMP. Por el contrario, Heidarieh et al hallaron una sensibilidad para este antibiótico menor al 20% en cepas M. abscessus aisladas en varias regiones de Irán (10,(27)(28)(29)(30).…”
Section: Discussionunclassified